METODE ESTIMASI PROPERTI KRITIS UAP-CAIR KOMPONEN MURNI ESTER - Hartantoa, Dhoni; Rahayu, Ibnu Eka; Wibowo, Bayu Tri (Semarang State University, 2013)
Biodiesel become eco-friendly renewable energy resources which is consisted of monoalkyl ester or long chain fatty acid from plants or animal. Biodiesel has more advantage than petrodiesel. Property of pure compound such as critical properties are the important thing to determine chemical mixtures behavior and also as base of equation of state. Joback method can show good results in estimating critical properties of monoalkyl ester.